REVERSIBLE VENTILATION SYSTEM FOR ADMINISTRATIVE BUILDINGS - Valery Yu. Kravchuk; Andrey G. Rymarov (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives To consider the possibility of applying the principle of reversing air flows for a centralised ventilation system; to develop a specific scheme for air exchange reversible ventilation, which will take into account the peculiarities of the microclimate of administrative buildings; to select the type of filling of the air-permeable element and justify this choice; to determine the conditions for changing the direction of air movement in the ventilation system and the area of its application; to form a list of equipment necessary for the operation of such a system; to consider the influence of supply and exhaust devices on the heat and humidity regime of claddings. Methods  To achieve this goal, the published thematic material was reviewed and a patent search carried out using Russian and European databases. Data on mathematical modelling of filtration in porous media and experimental results were used. A method for ventilating rooms in administrative building using the reversal of movement of supply and exhaust air streams along the same channels was applied. Results  Schemas for reversible ventilation systems are presented and their modes of operation considered. It is established that the idea of reversing ventilation flows has not yet been applied in the development of centralised ventilation systems. Based on these published materials, it was concluded that the proposed design of supply and exhaust devices can be used in practice. An original air exchange scheme for the ventilation of administrative buildings and design of supply and exhaust devices for this system are proposed. The conditions for changing the operating modes of the system and the scope of its application are determined. Conclusion The use of the proposed ventilation system allows normative air exchange to be provided without using a supply unit during the cold season. This application of airflow reversal allows the potential of natural forces to be used to the fullest extent to ensure the air exchange of the rooms.